Nonlinear Control of Flyback type DC to DC Converters: An Indirect Backstepping Approach - Seker, Murat; Zergeroğlu, Erkan (IEEE, 2011)
Flyback type DC to DC converters are basically a transformer-isolated version of the standard buck-boost converter. In this work, a nonlinear control methodology for the flyback type DC to DC converter is proposed. The proposed method uses a backstepping approach to regulate the corresponding current required to set the output voltage to its desired value as opposed to directly regulating the output voltage. Simulation results are presented to illustrate the effectiveness of the proposed method.
IEEE International Conference on Control Applications (CCA) -- SEP 28-30, 2011 -- Denver, CO
Keywords: DC to DC converters; Flyback Converter; Nonlinear Control; Backstepping